2009
DOI: 10.1002/ange.200901583
|View full text |Cite
|
Sign up to set email alerts
|

Biokompatible funktionalisierte zellgängige Polyglycerinmikrogele

Abstract: Gel für die Zelle: Eine neue Methode zur Herstellung biokompatibler Polyglycerinmikrogele mit einstellbaren Größen (25–100 nm; oben im Bild) und Oberflächenfunktionalisierung (rote Kugeln) wurde entwickelt. Fluoreszenzmikroskopische Messungen belegen, dass die Partikel durch endocytotische Mechanismen in die Zellen aufgenommen und intrazellulär in der perinuklearen Region lokalisiert werden (unten im Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(19 reference statements)
1
12
0
2
Order By: Relevance
“…For this purpose, we synthesized four clips modified with polyglycerol (PG) dendrons (2 and 3) of first and second generation ([G1.0] and [G2.0]) and with dendritic hyperbranched polyglycerols (HPG) (4 and 5) in the central unit as solubilizing units ( Figure 2). [5] In contrast to the perfectly branched glycerol dendrimers and dendrons, which have a degree of branching (DB) of 100 %, HPG is randomly branched but has a well-defined dendritic structure with a DB of 60 to 75 %. [4] Hyperbranched polyglycerols are "dendrimer like" polymers that exhibit good biocompatibility and are well-soluble in polar solvents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, we synthesized four clips modified with polyglycerol (PG) dendrons (2 and 3) of first and second generation ([G1.0] and [G2.0]) and with dendritic hyperbranched polyglycerols (HPG) (4 and 5) in the central unit as solubilizing units ( Figure 2). [5] In contrast to the perfectly branched glycerol dendrimers and dendrons, which have a degree of branching (DB) of 100 %, HPG is randomly branched but has a well-defined dendritic structure with a DB of 60 to 75 %. [4] Hyperbranched polyglycerols are "dendrimer like" polymers that exhibit good biocompatibility and are well-soluble in polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…PG dendrons have a unique design that is based on the extremely biocompatible glycerol building block. (3), HPG (1kDa) (4), and HPG (3kDa) (5). [5] In contrast to the perfectly branched glycerol dendrimers and dendrons, which have a degree of branching (DB) of 100 %, HPG is randomly branched but has a well-defined dendritic structure with a DB of 60 to 75 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mit dem Konzept lassen sich über inverse Miniemulationspolymerisation durch säurekatalysierte Polyaddition hochmolekulare Polyglycerinmikrogele mit bisher nicht erreichten Durchmessern von bis zu 80 nm und engen Größenverteilungen erzeugen 27. Auch diese sind nachträglich über z.…”
Section: Manipulation Modifizierung Und Design Nanoskaliger Objekteunclassified
“…Additionally, nPG show a high Young's modulus which is a sign of a rigid core structure, with the result that they have been much studied for their stiffness and size . In the search for new polymeric architectures that have a longer circulation half life in blood, the synthesis of different nPGs and studies of their physicochemical properties have been reported . In this paper, we synthesize polyglycerol amine nanogels and study the relation of charge density, their behavior during polyplex formation with DNA and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%